Human rights and jus Cogens: Questioning the use of normative hierarchy theory in human rights law - Mayua, Jim Nzonguma (Department of Public Law, 2014)
A Jus cogens is a hierarchically superior norm 'from which no derogation is permitted'. This peremptory norm suggests that there is a hierarchy among rules relating to international law. As such the recent trend of placing human rights norms in the catalogue of jus cogens has had a significant impact on both domestic and international law. For instance, in Barcelona Traction, Light and power Co, Ltd (Belgium v Spain), the International Court of Justice (ICJ), when making a distinction between the obligation of states towards the international community as whole and those arising vis-Ñ -vis another state, held that the former are obligation erga omnes in view of their importance